Process of change for people with knee osteoarthritis undergoing cognitive functional therapy: a replicated single-case experimental design study. - Caneiro, JP; O'Sullivan, Peter; Tan, Jay-Shan; Klem, Nardia-Rose; de Oliveira, Beatriz I.R.; Choong, Peter F; Dowsey, Michelle; Bunzli, Samantha; Smith, Anne (2023)
PURPOSE: To examine the applicability and process of change of Cognitive Functional Therapy (CFT) in the management of pain and disability in people with knee osteoarthritis who were offered knee replacement surgery and had risk factors for poor response to surgery. METHODS: Single-case experimental design with a mixed-methods, repeated measures approach was used to investigate the process of change through CFT in four participants. Qualitative interviews investigated beliefs, behaviours and coping responses, and self-reported measures assessed pain, disability, psychological factors, and function at 25 timepoints. Study registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12619001491156). RESULTS: Qualitative data indicate that CFT promoted helpful changes in all participants, with two responses observed. One reflected a clear shift to a biopsychosocial conceptualisation of osteoarthritis, behavioural re-engagement and the view that a knee replacement was no longer necessary. The other response reflected a mixed conceptualisation with dissonant beliefs about osteoarthritis and its management. Psychological and social factors were identified as potential treatment barriers. Overall, quantitative measures supported the qualitative findings. CONCLUSION: The process of change varies between and within individuals over time. Psychological and social barriers to treatment have implications for future intervention studies for the management of knee osteoarthritis.IMPLICATIONS FOR REHABILITATIONCognitive Functional Therapy is applicable in the management of knee osteoarthritis.Reconceptualisation of osteoarthritis reflected a helpful change.Psychological and social factors emerged as barriers to recovery.